A Review of Hybrid Generation Systems - H. Al-Tameemi, Zaid; H. Enawi, Hayder; A.Jumaa, Fadhel; K. Latif, Haider; K. Abbas, Mohammad (International Journal of Engineering and Technology, 2018)
The use of hybrid generators has been embraced widely as a modern way of producing sustainable energy. Particularly, this approach has been fundamental in the extension or the development of new power grids that have played an important role in powering the rural areas. From a different perspective, the hybrid power generators have played a key role in the management of various inefficiencies in the production of electricity. The production of electricity via diesel generators is subject to operational challenges related to the fluctuating prices of diesel. On the other hand, wind energy is intermittent in nature, hence a limited reliability. In this regard, it will be a remedial move to adopt the use of various hybrids to internalize these shortcomings. The advantages of one particular element in a given hybrid will compensate for the shortcomings of a given element within the same hybrid.Â  There exist a variety of hybrids that are used in the generation of electricity in the modern world. A typical hybrid will harness or store energy from two or more sources. Therefore, this paper will present a literature review of the nature of various hybrids that are used in the modern world. Some of these hybrids include; Wind-hydrogen system, Wind-hydro system, Wind-diesel system, Wind-compressed air system, and the Wind-solar system. These hybrids have been embraced to mitigate the intermittent nature of wind energy. Additionally, this paper will shed light on the impacts of these hybrids to the various societies in which they are deployed. Particular emphasis will also be laid on the distribution of these hybrids across the globe. Lastly, this paper will highlight the various problems that face these hybrid generators and offer recommendations and possible solutions.Â